Clinical manifestations of Graves’ disease among adults - a review of literature - Skoczylas, Kamila; Rokicki, Sebastian; Schok, Katarzyna; Mikulska, Julia (Journal of Education, Health and Sport, 2023)
Introduction: The most common cause of hyperthyroidism among adults is Graves' disease. The symptoms that occur in the course of this disease affect various systems and organs, including the skin, eyes, cardiovascular system, nervous system and respiratory system. The aim of the study: The aim of the work was to review available publications and materials and present the current state of knowledge on possible symptoms of Graves' disease among adults. Material and method: A review of publications available in the PubMed database was conducted. Articles were searched in English using keywords such as Graves' disease, hyperthyroidism, thyrotoxicosis, thyroid disease. Subsequently, works related to the subject of the publication were selected. Conclusions: Graves' disease is a fairly common endocrine disorder, but its diagnosis can be delayed due to the variety and non-specificity of symptoms. In untreated cases, hyperthyroidism can lead to a life-threatening condition. Effective antithyroid drugs are available, so it is important to remain vigilant and recommend monitoring thyroid function tests if there are suspicions of its dysfunction.